Um olhar sobre a interdisciplinaridade nas licenciaturas em educação do campo, nas ciências da natureza, no Rio Grande do Sul - Sául, Tamine Santos (2018)
The present research focuses on one of the specificities of Field Education, which is the interdisciplinarity, in the Degree in Field Education, in Nature Sciences, in the state of Rio Grande do Sul. Initially, with the objective to justify the research, it was necessary to search for the existing academic productions on the subject, in order to seek the articulations between Field Education and Science Teaching, from the Portal of Periodicals CAPES, from the Brazilian Digital Library of Theses and Dissertations (BDTD) and in the minutes of the National Meeting of Research in Education in Sciences (ENPEC). They formed the corpus of analysis of academic productions: 3 articles and 1 dissertation. With this, it was possible to perceive that the subject interdisciplinarity is little discussed in the academic productions of the area of the Sciences of Nature. Thus, the research problem emerges: In what way is interdisciplinarity presented and worked on in the Field Education Degrees in the Area of Natural Sciences in RS? To respond to this problem, the general objective of the research was to analyze how Interdisciplinarity has been presented and worked, as well as the specific objectives were to map the courses, to analyze how the interdisciplinarity is present in the Pedagogical Projects and to understand how the coordinations of the Courses comprise Interdisciplinarity and its challenges. After the mapping of the mentioned courses and the analysis of the Pedagogical Projects, the interviews with the coordinators were scheduled. The analysis took place through Discursive Textual Analysis and it was possible to identify three emergent final categories: 1. LEDOC's specifics (LEDOC's Area of Knowledge, The Pedagogy of Alternation (PA) as articulator of Interdisciplinarity in Ledoc's ' 2. Interdisciplinarity possibilities in Ledoc's (Axes, themes and study complexes, Generating Theme (TG), Interdisciplinarity disciplines in LEDOCs) and 3. Challenges to the practice of interdisciplinarity in Ledoc's. The analyzes allowed to identify that there are specifics for the Degree in Field Education present in the documents and that are being followed by the courses, which collaborate so that the interdisciplinarity happens. They also allow us to see that the courses have built strategies / possibilities, such as the formatting of semesters, disciplines and work based on themes. And yet, there were some challenges such as the importance of ongoing formation and spaces for collective discussions and planning.